Multiperiod Analysis of Adoption Motives: The Case of SFAS No. 106. - Amir, Eli; Livnat, Joshua (The Accounting Review, 1996)
Abstract Examines managers' adoption-timing motives related to Statement of Financial Accounting Standards (SFAS) No. 106. Government policy on postretirement benefits other than pensions (PRB); Earnings management; Adoption timing and PRB plan amendments.